MODERATING ROLE OF FAMILY CAPITAL ON THE RELATIONSHIP BETWEEN ENTREPRENEURIAL EXPOSURE AND FAMILY BUSINESS SUSTAINABILITY IN SOUTHEAST NIGERIA - Udu, Ama Aka; Okereke, Felix; Adegbola, Eunice; Azubuike-Bakare, Ogbonnia (African Journal of Social and Behavioural Sciences, 2025)
The study was on the moderating role of family capital on the effects of entrepreneurial exposure on family business sustainability in Southeast Nigeria. The study’s specific objectives were to determine how parental role modelling, financial capital, and social capital influenced entrepreneurial exposure and the sustainability relationship of family businesses in Southeast Nigeria. The study was anchored on social learning theory and sustainable family business theory. The sample size for the study was 520 small-scale businesses in Southeast Nigeria. Structured questionnaires were used to gather data from the respondents and were analysed through Haye’s Moderation Approach. The results showed that there was a significant positive relationship between parental role modelling and family business sustainability (r = 0.311, P < 0.000). It was discovered that financial capital impacts positively on family business sustainability (β = 0.6189, P = 0.0001) and social capital impacts positively on family business sustainability as well (β = 0.2762, P = 0.0238). It was found that financial capital and social capital do not moderate the effect of parental role modelling on family business sustainability (β = 0.0201, P = 0.0777; β = 0.2762, P = 0.0238) respectively. It was therefore recommended that to sustain a family business, there is a need to encourage entrepreneurial exposure among prospective successors and that the family capital should be improved.